Motivações para a sustentabilidade: o caso de três famílias de agricultores familiares, participantes do programa Cultivando Água Boa no município de Quatro Pontes - Feyh, Paulo César (2019)
The objective of our work is to know the motivations of family farmers in the Municipality of Quatro Pontes to participate in the Sustainability Program called Cultivating Good Water. Man's relationships with the environment in which he lives need to be revised, at the risk of not having future generations. This is the warning that, in the last century, several scholars and world leaders have testified in studies, world conferences and publications. Reviewing the trajectory of the debates on Sustainability and the understanding of concepts also brought with it the need to understand the motivation of the transforming agent of reality. Aristotle's contributions to understanding the human condition and the community sphere and Maslow's understanding of the mechanisms of human motivation were central to such an attempt. In this course we also analyzed the Good Water Cultivation Program (CAB) in the Municipality of Quatro Pontes, western region of Paraná, stating the farmers' perception of the same and the results obtained. For this we use a qualitative field research through the dialectical / phenomenological method. The benefits of CAB are undeniable in the lives of farmers, but when it comes to sustainability, we realize that the results are still limited in that the program does not become a state policy and remains only a government program.